PERTUMBUHAN DAN HASIL TANAMAN JAGUNG LOKAL SIGI (Zea mays L.) AKIBAT PEMBERIAN PUPUK NPK DAN LIMBAH CAIR TAHU - Jumriani A. Paerah; Indrianto Kadekoh; Jeki Jeki (Fakultas Pertanian, Universitas Tadulako, 2022)
The purpose of this study was to find the optimal rate of NPK fertilizer and tofu liquid waste for the best growth and yields of Sigi local corn plant. It was conducted at the Academic Garden located at Faculty of Agriculture, Tadulako University, from September to December 2021. This study used a two-factorial Randomized Group Design (RGD) with three replicates. The first factor was NPK fertilizer with four rates, namely control (N0), 100 kg/ha (N1), 200 kg/ha (N2) and 300 kg/ha (N3). The second factor is the tofu liquid waste with 4 levels, namely Control (L0), 10 ml/ l water (L1), 20 ml/l water (L2) and 30 ml/l water (L3). Data collected was analyzed using Analisys of Variance and Honest Tukey test. The results showed that there was no interaction effect between NPK fertilizer and tofu liquid waste on the growth and yields of Sigi local corn plant. The application of NPK fertilizers at a rate of 300 kg/ha resulted in improved growth of the corn plants specifically in term of leaf number, leeaf greenness, and stem diameter. On the other hand, it appears that the use of tofu liquid waste at concentrations ranging from 10 to 30 ml/L has not shown any significant improvement in growth or yield of the local corn plants.